THE INFLUENCE OF LEVERAGE, PROFITABILITY, DIVIDEND POLICY AND INVESTMENT OPPORTUNITY ON THE COMPANY VALUE - Arindalita Ajani; Anik Irawati; Mohd Fazli Mohd Sam (Prosiding International conference on Information Technology and Business (ICITB), 2019)
This study aims to obtain empirical evidence about the influence of leverage, profitability, dividend policy and investment opportunity on the company value in Indonesia and Malaysia banking company year 2012-2016. The method using in this research is purposive sampling method. The dependent variable in this research is company value by proxy PBV. Independent variable in this research is leverage, profitability, dividend policy and investment opportunity. This research is taken by the financial report and annual report of 10 banking companies with a total observation as much as 28 companies. Data analysis was performed with the classical assumption and hypothesis testing with multiple linear regression method. The result of this study show that leverage does not affect significantly on the company value, while the profitability, dividend policy, and investment opportunity has a positive and significant effect on the company value.Keywords: Leverage; Profitability; Dividend Policy; Investment Opportunity